Squamous cell carcinoma of the lower eyelid penetrating into the orbit – case report - Skowrońska, Nina; Szumiński, Michał; Bakunowicz-Łazarczyk, Alina; Pawłowski, Przemysław; Tomaszewski, Bożydar (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
The aim of our study is to report a case of pigmented squamous cell carcinoma of the palpebral conjunctiva referred to our clinic because of eye pain. A 86 year old patient suffering from eye pain due to a lower right eyelid tumour was admitted to our department. The basic ophthalmic examination and CT scans of orbits were performed. A lesion was surgically removed and histologically examined. The best corrected visual acuity in the left eye was 0.1 and there was light perception in the right eye. Ocular examination of the right eye revealed hard, pigmented and vascularized mass in the lower palpebral conjunctiva penetrating into the lid margin and the orbit, epiphora, bacterial conjunctivitis and vascularized corneal scar with adherent leucoma. Histopathologic examination revealed a squamous cell carcinoma. The accurate diagnosis and correct management of the malignant eyelid tumours always requires histological examination. Surgical removal and additional radiotherapy in the case of extensive SCC conjuctival lesions is necessary.